The expanding mycovirome of Aspergilli - Battersby,JL; Stevens,DA; Coutts,RHA; Havlíek,V; Hsu,JL; Sass,G; Kotta-Loizou,I (Journal of Fungi, 2024)
Mycoviruses are viruses that infect fungi and are widespread across all major fungal taxa,exhibiting great biological diversity. Since their discovery in the 1960s, researchers have observeda myriad of fungal phenotypes altered due to mycoviral infection. In this review, we examine thenuanced world of mycoviruses in the context of the medically and agriculturally important fungalgenus, Aspergillus. The advent of RNA sequencing has revealed a previous underestimate of viralprevalence in fungi, in particular linear single-stranded RNA viruses, and here we outline the diverseviral families known to date that contain mycoviruses infecting Aspergillus. Furthermore, we describethese novel mycoviruses, highlighting those with peculiar genome structures, such as a split RNAdependent RNA polymerase gene. Next, we delineate notable mycovirus-mediated phenotypesin Aspergillus, in particular reporting on observations of mycoviruses that affect their fungal host’svirulence and explore how this may relate to virus-mediated decreased stress tolerance. Furthermore,mycovirus effects on microbial competition and antifungal resistance are discussed. The factors thatinfluence the manifestation of these phenotypes, such as temperature, fungal life stage, and infectionwith multiple viruses, among others, are also evaluated. In addition, we attempt to elucidate themolecular mechanisms that underpin these phenotypes, examining how mycoviruses can be targets,triggers, and even suppressors of RNA silencing and how this can affect fungal gene expression andphenotypes. Finally, we highlight the potential therapeutic applications of mycoviruses and how, inan approach analogous to bacteriophage therapy, their ability to produce hypovirulence in Aspergillusmight be used to attenuate invasive aspergillosis infections in humans.